PENGARUH FAKTOR LINGKUNGAN BIOTIK DAN ABIOTIK TERHADAP KEJADIAN MALARIA DI KABUPATEN BANJARNEGARA - Tri Suryantoro; Bayu Suseno (Jurnal Ilmiah Medsains, 2020)
Of the 34 Health center areas, the incidence was found in eleven Puskesmas areas (1.54%) in 2017 as endemic areas. Based on data from the Banjarnegara District Health Office (2015), four sub-districts were declared as endemic areas. Subdistricts that investigated were 61 cases in Banjarmangu Subdistrict, 11 cases in Purwonegoro Subdistrict, 7 cases in Kalibening Subdistrict, and 4 cases in Purworejo Klampok. This study aims to determine the effect of the physical environment, on the perception of malaria endemic local community in Banjarnegara District, determine the effect of mosquito species on the perception of malaria endemic areas, Analyze the influence of the physical environment and mosquito species on community perception. This research is an explorative analytic. The total sampling of respondents was 45 malaria positive people at four sampling stations. The results of research conducted on malaria endemic areas of Banjarnegara Regency were two factors from the physical environment for the perception of the community in malaria endemic areas, namely humidity and wind speed. Mosquito species will not affect the community, but from the results of the spread of the number of species of Anopheles mosquitoes that found the station affected by the highest malaria incidence, namely in the Banjarmangu Subdistrict with a height varying between 500-1000masl which is a suitable height for Anopheles mosquito habitat as the main vector malaria.